STYLE PIDATO EMHA AINUN NADJIB DALAM “MERAJUT KEMBALI NUSANTARA” - Guntur Yuli Triasmoro (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2016)
This paper investigates the use  rhetorical dictions and language styles used in the speech of Emha Ainun Najib in “Rebuilding of Nusantara”. Qualitative approach was used in this study.  Data of this study were language aspects in the speeches focused on dictions and styles in the speeches performed by Emha Ainun Najib, entitled: “Rebulding of Nusantara”.  Data were obtained from www.youtube.com “Orasi Cak Nun Merajut Kembali Nusantara” (Oration of Cak Nun to Rebuild Nusantara). The study revealed diction in the speech of Cak Nun vary from connotative, denotative, five senses, locality, scientific, popular, general, abstract, concrete, and specific.  In addition, language styles in the speech include: paralellism, repetition, metaphor, persinification, simile, climax, erothetis, euphemism, and hyperbole.